The opportunities and challenges of empirical work: housing possession in theory and in practice - Bright, S; Whitehouse, L (Intersentia Uitgevers N V, 2014)
This book contains selected contributions from the third Young Property Lawyers Forum (YPLF) and the YPLF Masterclass 2012. It offers new perspectives on property theory, constitutional property law, and private law-property law. Under these headings, young and renowned property law scholars present their current research and offer an exciting look into the challenges property law faces in the 21st century. In November 2012 the YPLF met in Stellenbosch, South Africa for the Forum’s third edition. It is an informal network of young property law researchers that seeks to bring together property law researchers from around the world and to enable them to discuss their work with each other and with more experienced researchers. On this occasion a special Master Class was held after the YPLF in which some of the world’s leading property law scholars presented their research. The YPLF continues to form a network for property law researchers around the word, leading to more conferences and publications.